Pap Smear Screening Among the Postmenopausal Women - Demir, Berfu; Haberal, Ali; Ozturkoğlu, Esmen; Dündar, Betül; Baskan, Bahar; Sobacı, Emine; Özgül, Nejat (Gynecology Obstetrics & Reproductive Medicine, 2010)
OBJECTIVE: To evaluate the effectiveness of routine Pap smear screening in postmenopausal women. STUDY DESIGN: 2060 women applied to menopause outpatient clinic were reviewed retrospectively. Demographic characteristics, the use of hormone therapy, and the history of previous Pap smear were analyzed. RESULTS: The Pap smear results were as; normal in 1320, inflammation in 591, atrophy in 121, metaplasia in 22, ASCUS in 4, HGSIL in 1, and carcinoma in 1. While two of the ASCUS patients had two previous cervical smears which were normal; the other two HGSIL and carcinoma patient had not previous Pap smear. The patients who had ASCUS, colposcopy was applied and three of them were normal. The histopathological analysis of the cervical biopsy in the HGSIL case was squamous cell carcinoma. CONCLUSION: Pap smear screening should be done to postmenopausal women in spite of low efficiency or false positive results.